Effect of seasonal changes on fertility parameters of Holstein dairy cows in subtropical climate of Taiwan - Liu, Wen-Bor (Asian-Australas J Anim Sci, 2018)
OBJECTIVE: The purpose of this retrospective study was to investigate the relationship between temperature–humidity index (THI), season, and conception rate (CR) of Holstein cows in central Taiwan. METHODS: The mean performance and number of observations were statistically evaluated for various parameters, including age at first service, number of days open, gestation length, CR, and calving interval for different parities. RESULTS: The results indicate that the mean age at first service was 493.2 days; the gestation length was similar across all cows of different parities, ranging from 275.1 to 280.7 days. The overall CR of all inseminations was significantly lower in multiparous cows (47.26%±0.22%) than in heifers (57.14%±0.11%) (p<0.05). At THI>72 and during the hot season (from June to November), CRs for multiparous cows were significantly reduced compared to that for heifers, while the ratio remained unchanged among heifers for all seasons. CONCLUSION: To achieve a high CR, lactating cows should be bred in winter and spring (from December to May) from the start of the seasonal breeding program, whereas the heifer should be allowed to breed in summer and fall under the subtropical climate in Taiwan.